‘The way to a man's heart is through his gut microbiota’ – dietary pro- and prebiotics for the management of cardiovascular risk - Kieran Tuohy; Francesca Fava; Roberto Viola (2014)
The human gut microbiota has been identified as a possible novel CVD risk factor. This review aims to summarise recent insights connecting human gut microbiome activities with CVD and how such activities may be modulated by diet. Aberrant gut microbiota profiles have been associated with obesity, type 1 and type 2 diabetes and non-alcoholic fatty liver disease. Transfer of microbiota from obese animals induces metabolic disease and obesity in germ-free animals. Conversely, transfer of pathogen-free microbiota from lean healthy human donors to patients with metabolic disease can increase insulin sensitivity. Not only are aberrant microbiota profiles associated with metabolic disease, but the flux of metabolites derived from gut microbial metabolism of choline, phosphatidylcholine and l-carnitine has been shown to contribute directly to CVD pathology, providing one explanation for increased disease risk of eating too much red meat. Diet, especially high intake of fermentable fibres and plant polyphenols, appears to regulate microbial activities within the gut, supporting regulatory guidelines encouraging increased consumption of whole-plant foods (fruit, vegetables and whole-grain cereals), and providing the scientific rationale for the design of efficacious prebiotics. Similarly, recent human studies with carefully selected probiotic strains show that ingestion of viable microorganisms with the ability to hydrolyse bile salts can lower blood cholesterol, a recognised risk factor in CVD. Taken together such observations raise the intriguing possibility that gut microbiome modulation by whole-plant foods, probiotics and prebiotics may be at the base of healthy eating pyramids advised by regulatory agencies across the globe. In conclusion, dietary strategies which modulate the gut microbiota or their metabolic activities are emerging as efficacious tools for reducing CVD risk and indicate that indeed, the way to a healthy heart may be through a healthy gut microbiota.